2010
DOI: 10.1123/ijsnem.20.3.216
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Sago and Soy-Protein Supplementation During Endurance Cycling Exercise and Subsequent High-Intensity Endurance Capacity

Abstract: The purpose of the study was to investigate whether a combination of sago and soy protein ingested during moderate-intensity cycling exercise can improve subsequent high-intensity endurance capacity compared with a carbohydrate in the form of sago and with a placebo. The participants were 8 male recreational cyclists with age, weight, and VO2max of 21.5 +/- 1.1 yr, 63.3 +/- 2.4 kg, and 39.9 +/- 1.1 ml . kg(-1) . min(-1), respectively. The design of the study was a randomized, double-blind placebo-controlled cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 14 publications
0
41
0
Order By: Relevance
“…Though possible noncaloric mechanisms are largely unknown, recent work points to the possibility that PRO (with CHO) can favorably impact HR and/or RPE during exercise (Hall et al, 2013;Martinez-Lagunas et al, 2010;McCleave et al, 2011). The impact that PRO can have on HR may precipitate from altered intestinal absorption rates of sodium and water.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Though possible noncaloric mechanisms are largely unknown, recent work points to the possibility that PRO (with CHO) can favorably impact HR and/or RPE during exercise (Hall et al, 2013;Martinez-Lagunas et al, 2010;McCleave et al, 2011). The impact that PRO can have on HR may precipitate from altered intestinal absorption rates of sodium and water.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, HR was possibly lower with ALA compared with PLA at both 20-and 120-min of the constant-load phase. Perhaps this precipitated from the intestinal cotransport mechanism described above; ALA may have facilitated sodium and water absorption across the gut (Rowlands et al, 2012;Van Loon et al, 1996;Wapnir et al, 1988) thereby preserving plasma volume (Hall et al, 2013) and reducing HR. The importance of this response is questionable though considering that this did not elicit a lower RPE than PLA nor did the lower HR persist into the TT.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Southeast Asia is a region with over 600,000,000 inhabitants and a year-round tropical (warm-humid) climate, where sago ( Metroxylin sagu ) palms are widely distributed and their starch is used as an important dietary CHO source; 14 for example, Malaysia, Indonesia and Papua New Guinea are the world's leading countries in the production of sago 15 . Previous research has identified sago as being rapidly digestible, quickly absorbed and therefore suitable for consumption before, during and in recovery from exercise, 16 however only one study had initially tested this notion 17 before our recent series of investigations developing a reliable protocol to test whether supplementing sago before, during and in recovery indeed proved ergogenic 18-20 …”
Section: Introductionmentioning
confidence: 99%
“…Volume of oxygen exhaled (VO2), volume of carbon dioxide exhaled (VCO2), RER, minute ventilation (VE), and HR were recorded using 15 s averages during the TTE. The TTE was terminated when the exerciser failed to maintain ≥60 revolutions per minute for five consecutive seconds [23,24]. Blood lactate was taken immediately after TTE was terminated.…”
Section: Figurementioning
confidence: 99%